Synchronous multiple oral squamous cell carcinoma in a female patient: A case report and review (Indian Journal of Case Reports, 2017)
Oral squamous cell carcinoma (OSCC) is a common oncological problem in India. However, the frequency of developing synchronous carcinomas, i.e., development of second primary tumor (SPT) either simultaneously or within 6 months of the index tumor, in the orofacial region are rare and ranges from 8% to 21%. These lesions are more aggressive, treatment-resistant, and metastasize early. The onset of SPT decreases the 5-year survival by 18–30% as compared to those with a single tumor. Astonishingly, it was found that synchronous OSCCs showed 100% male predominance, with no female predilection. This case of synchronous OSCC in a 58-year-old female had an index tumor involving right side of the mandible and a SPT in the left buccal mucosa. Both the lesions were histopathologically diagnosed well-differentiated squamous cell carcinoma. Hence, the importance of reporting this case lies on the rarity, aggressiveness, and poor prognosis of the lesion and the patient being a female.